2017
DOI: 10.1111/imm.12711
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic cross‐reactivity between Schistosoma mansoni and peanut: a role for cross‐reactive carbohydrate determinants (CCDs) and implications for the hygiene hypothesis

Abstract: The antigenic reactivity of constituents of Schistosoma mansoni and peanut (Arachis hypogaea) was investigated to determine whether identical antigenic epitopes possessed by both organisms provided a possible explanation for the negative correlation between chronic schistosome infection and atopy to allergens. Aqueous extracts of peanuts were probed in Western immunoblots with rabbit IgG antibodies raised against the egg, cercarial and adult worm stages of S. mansoni. Several molecules in the peanut extract we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 77 publications
(159 reference statements)
0
23
0
Order By: Relevance
“…Through in vitro studies, rabbit anti‐schistosome IgG was found to cross‐react with allergens such as latex and peanut extract . The authors proposed that anti‐schistosome IgG antibodies may block IgE‐induced allergic responses and therefore prevent the manifestations of allergic disease …”
Section: Helminths and Allergy‐related Outcomes: Immune Mechanisms Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Through in vitro studies, rabbit anti‐schistosome IgG was found to cross‐react with allergens such as latex and peanut extract . The authors proposed that anti‐schistosome IgG antibodies may block IgE‐induced allergic responses and therefore prevent the manifestations of allergic disease …”
Section: Helminths and Allergy‐related Outcomes: Immune Mechanisms Inmentioning
confidence: 99%
“…65,66 Through in vitro studies, rabbit anti-schistosome IgG was found to cross-react with allergens such as latex 65 and peanut extract. 66 The authors proposed that anti-schistosome IgG antibodies may block IgE-induced allergic responses and therefore prevent the manifestations of allergic disease. 66 Generally, IgE to CCDs are not thought to be biologically active, but in recent years, responses to the mammalian carbohydrate epitope galactoseα-1,3-galactose (α-gal) have been of interest in the field of allergy since this epitope has been linked to two forms of anaphylaxis.…”
Section: Helminth-induced Ige Cross-reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of anti‐ Ascaris IgG4 have been negatively associated with allergen SPT positivity, while in a S. mansoni ‐endemic area—although higher levels of both IgE and IgG4 were found in infected individuals—a higher ratio of IgE to IgG4 predicted clinical allergic symptoms, just as in allergen‐specific immunotherapy . As many helminth products are homologous to common allergens, IgG4 responses raised against helminth products may also bind and block IgE epitopes on allergens, reducing responses to allergens and directly reducing SPT responses . Mechanistic research into the role of IgE and/or IgG4 is hampered by the lack of good experimental animal models, as IgG4 does not exist in mice.…”
Section: Helminths and Modulation Of Allergic Disease: The Role Of Immentioning
confidence: 99%
“…104 As many helminth products are homologous to common allergens, IgG4 responses raised against helminth products may also bind and block IgE epitopes on allergens, reducing responses to allergens and directly reducing SPT responses. [105][106][107] Mechanistic research into the role of IgE and/or IgG4 is hampered by the lack of good experimental animal models, as IgG4 does not exist in mice. of the parasitic infection.…”
Section: Igementioning
confidence: 99%